Home ventilation for children with chronic respiratory failure in Istanbul - KARADAĞ, BÜLENT TANER; KIYAN, GÜRSU (KARGER, 2008)
Background: The number of children on home mechanical ventilation (HMV) has increased markedly in Europe and North America but little is known about the HMV use and outcomes in children in Turkey. Objective: To review clinical conditions and outcome of children who were discharged from the hospital on respiratory support. Methods: Thirty-four patients assessed at the Marmara University Hospital in Istanbul who had been receiving ventilatory support at home for more than 3 months were included in the study. Results: Thirty-four patients with a median age of 5.1 years were discharged home with ventilatory support. HMV was started in 2001 at our institution and the number of children treated has increased substantially since then (2001: n = 1, 2002: n = 3, 2003: n = 3, 2004: n = 2, 2005: n = 14, 2006: n = 11). Ventilatory support was started at a median age of 1.8 years and continued for 13 months. Eleven (32.4%) patients received invasive mechanical ventilation via tracheostomy and 23 (67.6%) patients received noninvasive mechanical ventilation. Sixteen children (47.1%) were on noninvasive mechanical ventilation via nasal mask while 7 (20.6%) used a face mask. Seven (20.6%) patients received ventilatory support for 24 h and 27 (79.4%) patients were supported only during sleep. Twenty-four (70.6%) children received supplemental oxygen in addition to ventilatory support. Three patients successfully came off ventilatory support; 11 patients died during follow-up. None of the patients had home nursing and there were no life-threatening complications. Conclusions: A rapidly rising trend of HMV use in chronic respiratory failure (CRF) has been observed in this study. HMV can be safely applied in selected children with CRF with close monitoring and proper follow-up in developing countries despite the lack of home nursing. Copyright (C) 2007 S. Karger AG, Basel.
Keywords: mechanical ventilation, home; chronic respiratory failure; ventilatory support; mechanical ventilation, invasive; mechanical ventilation, noninvasive; MECHANICAL VENTILATION; CARE; TRACHEOSTOMY; SLEEP; PRESSURE; INFANTS; PEOPLE; RISK